Dataset for Study of the Electrocatalytic Hydrogenation of Benzaldehyde and Furfural at Heterostructured MoS2/N-Carbon Thin-Film Electrodes - Colavita, Paula; Schroder, Christian; Henderson, Lua (Colavita Group, Trinity College Dublin, 2025)
Electrocatalytic hydrogenation (ECH) has been proposed as a route to sustainable organic hydrogenations; however, development of low-cost and sustainable electrocatalyst materials for this reaction is still needed. Herein, we investigate thin-film heterostructured electrodes consisting of MoS2 supported at N-doped carbon in the ECH of carbonylated organics. Carbon-supported MoS2 is known to catalyze the hydrogen evolution reaction; however, its potential to activate hydrogen toward organic hydrogenations is poorly understood. Electrodes were fabricated using a combination of sputter deposition, thermal treatments, and CVD proximity growth, yielding thin-film electrodes with well-defined geometry, morphology, and N-functionality type. MoS2/N-carbon films were characterized via microscopy and Raman and X-ray absorption spectroscopy. Electrochemical methods were used to establish the loading of electroactive Mo centers and quantitatively assess their activity. The response of MoS2/N-carbon as an electrocatalyst in the ECH was first investigated via voltammetry and electrolysis using benzaldehyde as a diagnostic carbonylated compound. The turnover frequency (TOF) at Mo centers was estimated to be ca. 600 h–1 in 20 mM solutions at −0.6 V vs RHE, with 97% selectivity toward the alcohol vs the electrodimerization product. Performances were then studied using furfural, a substrate of interest for ECH applications to the stabilization of bio-oil. TOF of ca. 900 h–1 were obtained with 94% alcohol selectivity under the same conditions and, notably, no evidence of overhydrogenation, a common problem in the ECH of furfural. These results suggest that MoS2/N-carbon materials hold the potential to deliver competitive performances compared to precious metal electrocatalysts in the literature.
PUBLISHED